The determinats of e-learning usage by teachers of vocational high schools in the Yogyakarta Special Region - Priyanto Priyanto; Herminarto Sofyan; Herman Dwi Surjono (Jurnal Pendidikan Vokasi, 2017)
The purpose of the study was to find the determinants of e-learning implementation by teachers of vocational school in the Yogyakarta Special Region. The research objective was achieved by describing the essential influence of social environment and facilitating conditions toward the technology acceptance model of e-learning. The study was a correlational research one with an ex-post facto approach. The number of research sample was 132 teachers and the research sample was determined by the Krejcie & Morgan formula. The research sample was distributed by means of proportional random sampling technique. The primary data source was the teachers' self report which had been collected by using a questionnaire. The observation and the open-ended interviews were conducted in order to support the primary data. The content validity was assessed by means of expert judgment and the construct validity was calculated by means of Pearson correlation. The reliability was determined by means  of Cronbach's Alpha minimum value namely 0.70. The data analysis was performed by  using path analysis at a significance level of 0.05. The study concluded that the effect of social environment and facilitating conditions to the e-learning usage had been mediated by three main variables of Technology Acceptance Model (TAM), namely perceived usefulness, perceived ease of use, and intention to use.Keywords: E-learning, technology acceptance model, social environment, facilitating conditions. DETERMINAN PENGGUNAAN E-LEARNING OLEH GURU SMK DI DAERAH ISTIMEWA YOGYAKARTAAbstrakStudi ini bertujuan untuk mengetahui faktor determinan penggunaan e-learning oleh guru SMK di Daerah Istimewa Yogyakarta. Tujuan ini dicapai dengan cara menjelaskan hakikat pengaruh lingkungan sosial sekolah dan kondisi fasilitas teknologi terhadap model penerimaan teknologi e-learning. Studi ini merupakan penelitian korelasional bersifat ex-post facto. Sampel penelitian sebanyak 132 guru ditentukan menggunakan formula Krejcie & Morgan didistribusikan dengan teknik proportional random sampling. Sumber data primer adalah laporan diri guru, dikumpulkan menggunakan kuesioner. Observasi dan wawancara terbuka dilakukan sebagai pendukung data primer. Validasi isi dilakukan dengan expert judgment  dan validasi konstruk dilakukan dengan korelasi Pearson. Reliabilitas ditentukan dengan dengan nilai Cronbach's Alpha minimal 0,70. Analisis data dilakukan dengan analisis jalur pada taraf signifikansi 0,05. Hasil studi menunjukkan pengaruh lingkungan sosial dan kondisi yang memfasilitasi terhadap penggunaan e-learning dimediasi oleh tiga variabel utama model penerimaan teknologi, yaitu kegunaan, kemudahan penggunaan, dan intensi.Kata kunci: e-learning, model penerimaan teknologi, lingkungan sosial, kondisi yang memfasilitas